Shugosin 2 is a biomarker for pathological grading and survival prediction in patients with gliomas - Ying Kao (Nature Portfolio, 2021)
Abstract Glioblastomas are the most common type of adult primary brain neoplasms. Clinically, it is helpful to identify biomarkers to predict the survival of patients with gliomas due to its poor outcome. Shugoshin 2 (SGO2) is critical in cell division and cell cycle progression in eukaryotes. However, the association of SGO2 with pathological grading and survival in patients with gliomas remains unclear. We analyzed the association between SGO2 expression and clinical outcomes from Gene Expression Omnibus (GEO) dataset profiles, The Cancer Genome Atlas (TCGA), and Chinese Glioma Genome Atlas (CGGA). SGO2 mRNA and protein expression in normal brain tissue and glioma cell lines were investigated via quantitative RT-PCR, Western blot, and IHC staining. The roles of SGO2 in proliferation, migration, and apoptosis of GBM cells were studied with wound-healing assay, BrdU assay, cell cycle analysis, and JC-1 assay. The protein–protein interaction (PPI) was analyzed via Search Tool for the Retrieval of Interacting Genes/Proteins (STRING). SGO2 mRNA expression predicted higher grade gliomas than non-tumor brain tissues. Kaplan–Meier survival analysis showed that patients with high-grade gliomas with a higher SGO2 expression had worse survival outcomes. SGO2 mRNA and protein expression were upper regulated in gliomas than in normal brain tissue. Inhibition of SGO2 suppressed cell proliferation and migration. Also, PPI result showed SGO2 to be a potential hub protein, which was related to the expression of AURKB and FOXM1. SGO2 expression positively correlates with WHO pathological grading and patient survival, suggesting that SGO2 is a biomarker that is predictive of disease progression in patients with gliomas.